2012
DOI: 10.2174/157488912800673119
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in Psychiatric Practice

Abstract: Nutraceuticals can be defined as food components or active principles present in aliments which have positive effects for health and quality of life, including preventing or treating disorders. Herbal and "natural" food supplements are increasingly used to treat different psychiatric disorders, often as "self-prescribed" therapies. With factors such as chronic illness, poor health, emotional distress, and quality of life influencing the desire for complementary medicine, patients with comorbid medical and psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…The second relevant point is that a significant number of caregivers decided not to discuss the use of complementary and alternative medicine interventions with their doctor, despite a diffuse feeling that there would have been an open-minded approach to this kind of interventions. We agree with Dr Patel and colleagues that the 42% in their study population is much lower than the 80% reported by Kompoliti et al 7 ; however, as Dr Patel and colleagues mention in their article, these interventions pose significant concerns in terms of safety 8 and interactions 9 with other treatments. Moreover, 17% of caregivers reported significant side effects, whose management could have been difficult without knowing about the complementary and alternative medicine interventions used.…”
supporting
confidence: 60%
“…The second relevant point is that a significant number of caregivers decided not to discuss the use of complementary and alternative medicine interventions with their doctor, despite a diffuse feeling that there would have been an open-minded approach to this kind of interventions. We agree with Dr Patel and colleagues that the 42% in their study population is much lower than the 80% reported by Kompoliti et al 7 ; however, as Dr Patel and colleagues mention in their article, these interventions pose significant concerns in terms of safety 8 and interactions 9 with other treatments. Moreover, 17% of caregivers reported significant side effects, whose management could have been difficult without knowing about the complementary and alternative medicine interventions used.…”
supporting
confidence: 60%
“…Given that PUFA administration is a highly safe intervention, it is important for the general pediatrician, to be aware of this option, of its possible use, of the differences existing between different products in order to best serve the interest of the patient and of his/her family, considering the increasing use of nutraceuticals in psychiatric e neuropsychiatric disorders [17]. It is also important to consider PUFAs as part of a more comprehensive approach towards neurodevelopmental difficulties, as evidenced by the clinical vignettes described.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is a collection of colonies of multiple microbes that reside in the body and live in a symbiotic relationship with their host [63]. The brain-gutmicrobiota axis comprises a part of this microbiota that is an extensive communication network between the brain [64] and gut.…”
Section: Interaction Between Nutraceuticals and The Gut Microbiotamentioning
confidence: 99%
“…This axis plays an important role in the emotional and cognitive development of an individual, and any dysbiosis in this axis will lead to the occurrence of neuropsychiatric illnesses [65,66]. Recent studies have shown the interaction between hypothalamo-pituitary-adrenal (HPA) axis and braingut-microbiota axis in the causation of psychiatric disorders [63].…”
Section: Interaction Between Nutraceuticals and The Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation